Asparagine Synthetase in Zea mays - Ross, Donald W. (My University, 1979)
In legume cotyledons, asparagine is synthesized by a transfer of the amide nitrogen of glutamine to aspartate. The asparagine synthetase reaction requires ATP-Mg²⁺, aspartate and glutamine as substrates, although NH₄Cl can act as a rather inefficient nitrogen donor.
In this project, asparagine synthetase was studied in extracts from several maize tissues. Enzyme activity (in nmoles asparagine per 20 minutes per gram fresh weight) was about 30 in developing endosperm and root tips, 60 in developing embryos, and 150 in scutella and mature root of seedlings.
Asparagine (2.0 mM) resulted in a 50% inhibition of the reaction in endosperm extract; 10 mM asparagine on the other hand inhibited the mature root and scutellar reactions less than 30%. The potential end products AMP and ADP inhibited the mature root reaction pore strongly than the scutellar reaction. Glutamate (10 mM) did not inhibit the scutellar reaction.
The addition of 1.0% bovine serum albumin to a crude extract from mature roots did not affect enzyme activity; however albumin doubled enzyme activity in mature root extract that had been filtered through Sephadex.
Km values obtained for glutamine in embryo, scutellar, mature root and soybean cotyledon extracts were 1.6, 0.49, 0.59, and 0.18 mM, respectively. Km values for NH₄Cl were 4.0, 2.6, 2.6 and 2.9 mM. These values indicate that the soybean enzyme reacts much more efficiently with glutamine than with NH₄Cl, but that the enzyme from various maize tissues reacts only slightly better with glutamine.
Glutamine protected the enzyme from heat inactivation in extracts from four maize tissues; however, its effect on mature root enzyme was much less pronounced than on embryo, scutellar or endosperm enzyme. NH₄Cl had little effect on the rate of inactivation in any of the four extracts.
Keywords: Biology; Biology